The Challenge of Pulmonary Nontuberculous Mycobacterial Infection - Novosad, Shannon (Curr Pulmonol Rep, 2015)
The incidence of nontuberculous mycobacterial (NTM) lung disease is increasing. Current treatment strategies are largely based on expert opinion. The lack of randomized clinical trials to inform treatment leave clinicians with many questions regarding the most effective and safe regimens. The risk-benefit ratio of therapy is often thought to favor observation given the chronic nature of the disease, multiple long-term antibiotics recommended for therapy, side effects associated with treatment, and perceived lack of efficacious therapies.